2013
DOI: 10.11646/zootaxa.3721.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Crenicichla taikyra (Teleostei: Cichlidae), a new species of pike cichlid from the middle río Paraná, Argentina

Abstract: Crenicichla taikyra, new species, is described from the middle río Paraná, Argentina. Crenicichla taikyra is distinguished from the other species of the genus by the following combination of characters: lower pharyngeal tooth plate stout, bearing molariform teeth, ascending arm of premaxilla longer than the dentigerous arm, posterior edge of preoperculum serrated, a well developed suborbital stripe, and absence of scattered dark dots on flanks. Molariform teeth on pharyngeal jaws is a derived character among C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…e . durophagy (Lucena & Kullander, ; Wainwright, ; Burress et al , ; Casciotta et al , ). Congruent with this expectation, Zuanon () showed that the diet of T .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…e . durophagy (Lucena & Kullander, ; Wainwright, ; Burress et al , ; Casciotta et al , ). Congruent with this expectation, Zuanon () showed that the diet of T .…”
Section: Discussionmentioning
confidence: 66%
“…Molariform pharyngeal teeth are known in few species of different putative lineages within Crenicichla and this condition is commonly linked to the specialized consumption of hard-shelled items, i.e. durophagy (Lucena & Kullander, 1992;Wainwright, 2006;Burress et al, 2013;Casciotta et al, 2013). Congruent with this expectation, Zuanon (1999) showed that the diet of T. preta is predominantly composed of hard-shelled gastropods, bivalves and caddisfly larvae (Trichoptera: Helicopsychidae) that make protective hard cases with sand grains (Wiggins, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The report of the cichlid C. missioneira as a consumer of L. fortunei is novel, although at least two other species of the same genus were also reported as mussel consumers (e.g. Casciotta et al, ; Lopes, ; Montalto, Oliveros, Ezcurra de Drago, & Demonte, ). In the case of the small‐sized Crenicichla species (maximum size of about 25 cm), its large and protractile mouth and strong pharyngeal teeth might be the key that allows them to feed and crush smaller mussels.…”
Section: Discussionmentioning
confidence: 98%
“…These publications, however, do not treat C. ocellata in the main text, but merely list the holotype among the examined material (e.g. Piálek et al 2010, 2015; Casciotta et al 2013; Říčan et al 2017). In one publication, these authors list C. ocellata unter its original name Boggiania ocellata (Piálek et al 2010), indicating that the authors did not intend to recognize B. ocellata as a distinct species, but used its original name to indicate the holotype.…”
Section: Discussionmentioning
confidence: 99%